Dependence of Interlayer Distance on the Charge Transfer Reaction of Ni-Al Layered Double Hydroxides. (5th January 2017) - Maki, Hideshi; Inoue, Masayoshi; Mizuhata, Minoru
Abstract : Ni-Al layered double hydroxide (LDH) is anode materials of the nickel metal hydride battery for high electrochemistry properties because of its structural stability of alkali electrolyte and smallness of volume change in the case of charge and discharge. LDH has interlayer anionic exchange property and changes at the interlayer distance by anionic exchange. In this study, Ni-Al LDH was synthesized by Liquid phase deposition (LPD) method and its interlayer distance was extended by anionic exchange. Then electrodes were made by the anion-exchanged LDH and checked relations between interlayer distance and internal resistance. Interlayer distances of Ni-Al LDH which calculated from d 003 values increase with the diameters of intercalated anions. The interlayer distance of LDH depends on the molecular shape and size of intercalated anions. The decrease of charge transfer resistance is obviously observed at about 300-400 pm of LDH interlayer distance, and the activation energy for charge transfer also decrease with the increasing of LDH interlayer distance.